Pemberdayaan Masyarakat melalui Inovasi Pengolahan Ikan Nila menjadi Kerupuk Bernilai Jual Tinggi di Desa Mata Mamplam - Zahraini Zahraini; Nurhayati Nurhayati; Surya Darni; Sutan Febriansyah; Rahimi Rahimi; Nurul Fadhila; Rahmatul Ulya; Milu Muspika Andini; Fisma Wani; Hasnawati Hasnawati; Liza Fadhila (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service activity was motivated by the community's limited knowledge and skills in processing Nile tilapia into economically valuable products. The approach used was participatory counseling and training, including material delivery, practical demonstrations, discussions, and evaluation through pretest and posttest. The program involved 30 participants, consisting of housewives and local fishery entrepreneurs. The results showed an improvement in participants' understanding, with the average pretest score of 61.10 increasing to 82.23 in the posttest, along with the ability to comprehend all processing stages from raw material selection to packaging. This activity also encouraged the community's interest in developing fish-based businesses as an alternative means to increase household income and contributed to economic empowerment as well as strengthened participation in the development of local products.